2015
DOI: 10.5539/gjhs.v8n3p37
|View full text |Cite
|
Sign up to set email alerts
|

Predictors of Mortality in Patients Undergoing Mitral Valve Replacement

Abstract: Objective:Although mitral valve replacement is frequently performed in patients of all age groups, there are few studies available which determine the causes of operative mortality in mitral valve replacement especially in our region. Therefore, the objective of this study was to identify factors that are significantly associated with operative mortality in mitral valve replacement.Methods:From August 2012 to March 2013, 80 consecutive patients undergoing mitral valve replacement in a single tertiary hospital … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
14
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 11 publications
1
14
1
Order By: Relevance
“…Age, for example, has already been identified as an important predictor numerous times [ 4 , 7 , 8 , 12 - 14 , 18 - 21 ] , in agreement with what was found here. On the other hand, a number of other studies did not show its relationship with worse outcome [ 11 ] or even identified the inverse relationship [ 22 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Age, for example, has already been identified as an important predictor numerous times [ 4 , 7 , 8 , 12 - 14 , 18 - 21 ] , in agreement with what was found here. On the other hand, a number of other studies did not show its relationship with worse outcome [ 11 ] or even identified the inverse relationship [ 22 ] .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have identi ed predictors of mortality in different patient populations undergoing valve surgery. In those undergoing mitral valve replacement, postoperative higher creatinine, low cardiac output, small mitral valve size, and new-onset atrial brillation were signi cant independent predictors of morality [9].…”
Section: Discussionmentioning
confidence: 96%
“…Mitral valve dysfunction (MVD) due to rheumatic heart disease (RHD) is the most frequently encountered surgical disorder in the developing world [1,2]. With the help of medical treatment, patients experiencing symptoms attain improvement, but the therapy of choice is surgical intervention, either mitral valve repair or replacement (MVR/r) [3].…”
Section: Introductionmentioning
confidence: 99%
“…Patients with untreated degenerative MVD have substandard projection, with annual death rates reaching up to 34% [5]. While the untreated rheumatic MVD (rMVD) mortality rate and predictors of outcome after rMVD surgery are yet to be explored, one study from the same region has reported operative mortality of 15% in 80 patients undergoing MVR [2].…”
Section: Introductionmentioning
confidence: 99%